Qualidade espermática de garanhões Mangalarga Marchador: influência da idade, peso e suplementação com ácidos graxos poliinsaturados ômega 3 - Rodrigues, Paula Gomes (2013)
The objective was to evaluate the influence of omega-3 supplementation, body condition score (BCS) weight and age on the quality of fresh, cooled and frozen-thawed Mangalarga Marchador stallion semen. Ten stallions were used (3.5 to 15 years-old; 389 ± 39.7 kg) allocated randomly to the following treatments: 150 mL of omega-3 enriched oil (n=10) and no supplementation (n=10). Stallions were switched over in the treatments after a 20 day interval. Semen was collected every fifteen days during 60 days, for a total of five samples per animal (n= 100 samples). The following seminal characteristics were evaluated: motility, vigor, viability, morphology, osmotic tolerance test (OTT), and lipid peroxidation of the plasma membrane. Semen was evaluated upon sampling and at 2, 6, 12 and 24 hours after cooling and 24 hours after freezing. Body weight was estimated at heart girth by means of a commercial tape and the BCS was based on a scale from 1-thin to 9-obese. The fixed effects of treatment, age and weight and samples were submitted to the Mixed Procedure of SAS® and means were compared by the orthogonal contrast. Vigor was higher in stallions older than four years and the index of morphological defects was lower in animals weighing more than 400 kg. In the fresh semen motility was greater in supplemented stallions. In frozen semen, motility, progressive motility, vigor and OTT were superior in the supplemented animals. In conclusion, the utilization of animals older than four years and weighing more than 400 kg and, moreover, the addition of omega-3 in the diet increases semen motility and vigor of fresh and frozen semen, maximizing its quality.